Advertisement Remove all ads

Using Properties of Determinants, Prove That: `|(1+A^2-b^2, 2ab, -2b),(2ab, 1-a^2+B^2, 2a),(2b, -2a, 1-a^2-b^2)| = (1 + A^2 + B^2)^3` - Mathematics

Using properties of determinants, prove that:

`|(1+a^2-b^2, 2ab, -2b),(2ab, 1-a^2+b^2, 2a),(2b, -2a, 1-a^2-b^2)| = (1 + a^2 + b^2)^3`

Advertisement Remove all ads

Solution

`|(1+a^2-b^2, 2ab, -2b),(2ab, 1-a^2+b^2, 2a),(2b, -2a, 1-a^2-b^2)| = (1 + a^2 + b^2)^3`

Let

`Delta = |(1+a^2-b^2, 2ab, -2b),(2ab, 1-a^2+b^2, 2a),(2b, -2a, 1-a^2-b^2)|`

We shall try to introduce zeros at a many places as possible keeping in mind that we have to introduce the factor `1 + a^2 +  b^2`

Applying `C_1 -> C_1 - bC_3` and `C_2 -> C_2 +  aC_3` we get

`Delta = |(1+a^2+b^2, 0, -2b),(0, 1+a^2+b^2, 2a), (b(1+a^2 +b^2), -a(1+a^2+b^2), 1-a^2 - b^2)|`

`=> Delta = (1 + a^2  +b^2)^2 |(1,0,-2b),(0,1,2a),(b, -a, -a^2-b^2)|`   [Taking `(1+ a^2 + b^2)` common from both `C_1 and C_2`]

`=> Delta = (1+ a^2 + b^2)^2 |(1,0,-2b),(0,1, 2a),(0,0, 1+z^2+b^2) |`       [Applying `R_3 -> R_3- bR_1 + aR_2`]

`=> Delta= (1 + a^2 + b^2)^2 xx 1 xx |(1, 2a),(0, 1+a^2 + b^2)|`       [Expanding along `C_1`]

`=> Delta= (1 + a^2 + b^2 )^3`

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×